PENGGUNAAN ALIH KODE PADA PERCAKAPAN DALAM DRAMA 5 JI KARA 9 JI MADE - Maharani, Elsa; Rahayu, Nana; Nimashita, Hana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is aimed to describe the code switching used on a conversation in 5 Ji Kara 9 Ji Made drama. The purpose of this research is to determine the type of code and the causes of code switching. The object of research in the form of 5 Ji Kara 9 Made drama. This research is a qualitative descriptive method. The results of this research were (1) There are 14 data using code switching in dialogue conversations, 10 data included into the type of code switching situational and 4 data is included into the type of code metaphorical (2) the causes of the code switching caused by the speaker, the person said and hearer as: changing the situation from the formal into informal, to benefit themselves, to reinforce their opinions and to demonstrate the ability of a foreign language to the listener. Each of code used by each speaker through the communication to explain what has been achieved from the speech uttered by each speaker where the speech has its own meaning and purpose.Keywords: sociolinguistics, code switching, drama.